2021
DOI: 10.1177/08862605211003168
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Economic Abuse Experiences: Results from the UN Multi-Country Study on Men and Violence in Asia and the Pacific

Abstract: Economic abuse is a poorly understood form of intimate partner violence but may have far-reaching implications for the financial health of the survivor. Additionally, very little is known about whether depressive symptoms, education, employment, or attitudes about relations between men and women mediate or moderate the relationship between economic abuse and their financial circumstances. The purpose of this study was to answer these two research questions: (a) Is there a relationship between the experience of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Three articles came from Turkey [32][33][34], two came from South Africa [35,36] and one article came from Germany [37], Ghana [38], Hong Kong [39], India [40], Malaysia [41], and Palestine [42]. A single article used data collected as part of a multi-country study of China, Cambodia, Papua New Guinea, and Sri Lanka [43].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three articles came from Turkey [32][33][34], two came from South Africa [35,36] and one article came from Germany [37], Ghana [38], Hong Kong [39], India [40], Malaysia [41], and Palestine [42]. A single article used data collected as part of a multi-country study of China, Cambodia, Papua New Guinea, and Sri Lanka [43].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All but two studies [39,41] had entirely female samples. The race/ethnicity of the sample was not documented in 12 studies [30,[32][33][34][36][37][38][39][40][41][42][43]. Six of the studies reported having a sample in which 50% or more identi ed as white [3,4,18,28,29,31].…”
Section: Samplementioning
confidence: 99%
See 2 more Smart Citations
“…Additional surveys have asked about sexual practices and behaviours across multiple countries. However, these range in quality (for example in terms of their representativeness [ 6 ]), the detail that they capture on sexual practices and behaviours, and the demographics of their target population [ 7 , 8 ]. Together, these data provide a patchy, but important base understanding of some sexual practices and behaviours for some populations at specific stages across the life course.…”
Section: Introductionmentioning
confidence: 99%